¡Pero vuelve a pasar! Una lectura psicoanalítica de la repetición del asesinato del líder defensor de derechos por ideología política en Colombia (2019)
The systematic murder of human rights defenders leaders, has emerged as a social symptom that is repeated in Colombia, obeying to the dynamics of violence in the country, even after the signing of the peace agreement in 2016. This research seeks to find the relationship between political ideology and repeat, with regard to the Act of murdering the leading advocate of rights. It conducted a psychoanalytic theoretical review of the paternal role, issues of political ideology and the compulsion to repeat the Act of murdering the leading advocate of rights, who is the representation of an imaginary father, but whose death is real and then it becomes a symbolic father.